Inquiry Exploration in Science Literacy: Learning Innovation in School of Life Lebah Putih - Nugraheni, Setyo Wuri Kartika; Wijayanti, Adek Candra Nur; Kuswanto, Sabar; Jupriyanto, Jupriyanto (INDONESIAN JOURNAL OF SUSTAINABILITY, 2026)
Scientific literacy is an essential competency for students; however, science learning in primary schools is often dominated by teacher-centered methods that limit student engagement and conceptual understanding. This study aims to describe the implementation of an inquiry-based approach in strengthening Disciplinary Core Ideas, mapping Science and Engineering Practices skills, and analyzing the relationship between scientific concepts and Crosscutting Concepts at School of Life Lebah Putih. This research employed a qualitative case study design involving semi-structured interviews with the principal, teachers, and students. The findings indicate that the inquiry-based approach enhances students’ active participation, conceptual understanding, and the relevance of science learning to everyday life, although its implementation is constrained by teachers’ reliance on lecture-based instruction. It can be concluded that inquiry-based learning has strong potential to improve scientific literacy in primary education; therefore, the development of locally contextualized learning modules is recommended to support more effective and sustainable implementation aligned with NGSS standards.Keywords: Science Literacy; Inquiry Approach; Basic Education